2013
DOI: 10.1111/ibi.12059
|View full text |Cite
|
Sign up to set email alerts
|

Temporal genetic structure and relatedness in the Tufted DuckAythya fuligulasuggests limited kin association in winter

Abstract: Conspecific aggregation of waterfowl in winter is a common example of animal flocking behaviour, yet patterns of relatedness and temporal substructure in such social groups remain poorly understood even in common species. A previous study based on mark‐recapture data showed that Tufted Ducks Aythya fuligula caught on the same day were re‐caught together in subsequent winters more often than expected by chance, suggesting stable assortments of ‘socially familiar’ individuals between wintering periods. The genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…; Liu et al . ). However, although our study revealed no relation between kinship and social structure, it was somewhat surprising that many individuals did appear to have at least one close relative ( r ≥ 0.25) in the population.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Liu et al . ). However, although our study revealed no relation between kinship and social structure, it was somewhat surprising that many individuals did appear to have at least one close relative ( r ≥ 0.25) in the population.…”
Section: Discussionmentioning
confidence: 97%
“…this study; tufted duck ( Aythya fuligula ) Liu et al . ). These patterns of variation provide opportunities for exploring how ecological factors interact with kinship to produce variations in the structures of animal societies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Juvenile king eiders (S. spectabilis) appeared not to migrate with their mother to the wintering area (Bentzen & Powell, 2015), but young common eiders and harlequin ducks (Histrionicus histrionicus) may follow their mother (Franzmann, 1983;Regehr et al, 2001). In tufted duck (Aythya fuligula) some same-sex close relatives occurred together in wintering areas (Liu, Keller & Heckel, 2013). Relatedness in brood parasitism and merging may partly be outcomes of a more general strategy in female waterfowl of associating with kin, with potential inclusive fitness benefits in several social situations (Andersson & Waldeck, 2007).…”
Section: (4) Kin Association Outside the Breeding Seasonmentioning
confidence: 99%
“…This supports the possibility that winter pairing contributes to the avoidance of inbreeding. The level of genetic variation within Northern Pintail and other dabbling duck populations might result from gene flow that is determined in the wintering grounds (Robertson & Cooke 1999, Scribner et al 2001, Liu et al 2013.…”
Section: Discussionmentioning
confidence: 99%